The Cyclical Nature of North-South FDI Flows - Eduardo Levy Yeyati; Ugo Panizza; Ernesto H. Stein (Inter-American Development Bank, Research Department, 2003)
In this paper, we examine how the business and interest rate cycles in developed countries affect FDI to developing countries. After aggregating flows into three big source areas (the U. S. , Europe and Japan), we find FDI flows to be countercyclical with respect to both output and interest rate cycles in the first two, whereas in Japan they display either no cyclical behavior or mild procyclical behavior. This finding is consistent with the fact that FDI outflows and local investment tend to move in opposite directions during the cycles in the U. S. and Europe, reflecting investors` arbitrage among different investment opportunities. In sum, and contrary to what is usually claimed, we conclude that recessions in industrial countries are likely to increase FDI flows, particularly to those countries with close ties with the U. S. and Europe.
Keywords: 330; Auslandsinvestition; Konjunktur; Zins; Entwicklungsländer